2017
DOI: 10.1038/s41562-017-0102
|View full text |Cite
|
Sign up to set email alerts
|

The functional brain networks that underlie Early Stone Age tool manufacture

Abstract: After 800,000 years of making simple Oldowan tools, early humans began manufacturing Acheulian handaxes around 1.75 million years ago. This advance is hypothesized to reflect an evolutionary change in hominin cognition and language abilities. We used a neuroarchaeology approach to investigate this hypothesis, recording brain activity using functional near-infrared spectroscopy as modern human participants learned to make Oldowan and Acheulian stone tools in either a verbal or nonverbal training context. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
94
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 62 publications
9
94
1
1
Order By: Relevance
“…information for higher-level behaviors (Putt et al, 2017;Stout & Chaminade, 2012). In line with previous hypotheses (Brass et al, 2009), we speculate that these incorporation processes may intervene at an intermediate stage between the processing of purely verbal information (likely involving language areas of the left hemisphere-a possibility entertained by Hartstra et al, 2011) and a sensorimotor stage in which verbally conveyed stimulusresponse mappings have been transformed into concrete sensorimotor representations for impending action.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…information for higher-level behaviors (Putt et al, 2017;Stout & Chaminade, 2012). In line with previous hypotheses (Brass et al, 2009), we speculate that these incorporation processes may intervene at an intermediate stage between the processing of purely verbal information (likely involving language areas of the left hemisphere-a possibility entertained by Hartstra et al, 2011) and a sensorimotor stage in which verbally conveyed stimulusresponse mappings have been transformed into concrete sensorimotor representations for impending action.…”
supporting
confidence: 54%
“…Consistent with Ruge and Wolfensteller's (2010) findings, these authors reported a cluster of activity within the rMFG-dPMC in the implementation group only. Together with evidence for right LPFC involvement in praxis-related integration of verbal instructions (Putt, Wijeakumar, Franciscus, & Spencer, 2017), these findings further suggest a role of this brain sector in translating verbal instructions into motor programs for accurate behavior.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…This includes evidence of increased functional activation during action execution 17,32 and observation 18 , as well as structural remodeling of underlying white matter in response to tool-making training 19 . To date, these findings have been interpreted using reverse inference from known functions of rIFG, including especially its involvement in the cognitive control functions of inhibition 33 and action updating 34 that are critical to response selection during multi-component behavior 35 .…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…There is a broad spectrum of social learning strategies across human cultures and across animal species, ranging from unsupervised observation to interactive teaching [36][37][38][39][40][41]. Prehistoric hominins could have used any of these learning strategies [28,[42][43][44]. Before the emergence of teaching, hominin children would have engaged in social learning through observation.…”
Section: Introductionmentioning
confidence: 99%